Sejarah lahirnya commonwealth Of Australia - Anita; Chairunisa Muh.Said (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to find out about the history of the birth of the Commonwealth of Australia, the method used in this study is qualitative research with library methods, the results of the study show that the Australian nation which is predominantly white and has a socio-cultural and socio-political background of England which is classified as Western as we know it today, starting from the British colony which was born in 1788 and was named New South Wales, outside the initial settlement, namely Port Jackson which developed into the city of Sydney today, then new settlements were also born such as Tasmania which was originally called Van Diemen's Land (starting in 1804), Queensland which was originally called the Moreton Bay District (starting in 1824), Victoria which was originally called the Port Philip District (starting in 1834/1835). In July 1900, the British parliament issued a law containing the Australian Constitution, but the constitution only came into effect on January 1, 190. Meanwhile, Western Australia also held a referendum and agreed to join the Commonwealth of Australia.